UJI KETAHANAN TIGA VARIETAS TOMAT (SOLANUM LYCOPERSICUM L.) TERHADAP SERANGAN CMV (CUCUMBER MOSAIC VIRUS) DENGAN METODE DAS-ELISA - Lia Agturani Tudaryati; Febi Nurilmala; Krisna Dwiharniati (Universitas Nusa Bangsa, 2011)
Endurance Test Three Tomato Variety (Solanum lycopersicum L.) Against Attacks CMV (Cucumber Mosaic Virus) DAS-ELISA Method Tomato plantation intensification can be done by controlling nuisance organism plant causes disease in tomato, such as CMV. CMV can be transmitted mechanically, and therefore testing of tomato varieties resistance to CMV can be performed with CMV isolates infect mechanically to healthy tomato plants (variety Marta F1, San Marino, and Viccario). CMV isolates derived from two sources, namely a positive tomato plants attacked by CMV (plant sap) and the positive control CMV AGDIA producers commonly used as a positive control test DAS-ELISA (Double Antibody Sandwich-Enzyme Linked immunosorbent assay). This study aims to test three varieties of tomato resistance against CMV attacks. Research conducted in the screen house and laboratory virology Central Agricultural Quarantine Standards Test. Identification of CMV infection was done by observing the incubation period, symptoms appeared, and continued with DAS-ELISA test. Structured treatment completely randomized design (CRD) with 6 replications. Data processed with fingerprint analysis and continued with various multiple Duncan test at 5% level test. The results showed the disease symptoms appeared only on the varieties of San Marino from CMV infected plant sap. Symptoms caused a reduction of leaf rolling and leaf lamina 8-10 day incubation period and symptoms of stunted stems with 14-28 day incubation period, the San Marino CMV causes the reduction of plant height by 33%. Sensitivity of tomato varieties against CMV San Marino sap from plants was quantitatively evidenced by positive results on the DAS-ELISA test. Meanwhile, F1 and Marta varieties resistant to Viccario CMV infection sap from plants and the positive control CMV AGDIA producers. Keywords : Tomato (Solanum Lycopersicum l.), Cucumber Mosaic Virus, DAS-ELISA method ABSTRAK Intensifikasi perkebunan tomat dapat dilakukan dengan mengendalikan organisme pengganggu tanaman (OPT) penyebab penyakit pada tomat, seperti CMV. CMV dapat ditularkan secara mekanis, oleh karena itu pengujian ketahanan varietas tomat terhadap CMV dapat dilakukan dengan menularkan isolat CMV secara mekanik kepada tanaman tomat sehat (varietas Marta F1, San Marino, dan Viccario). Isolat CMV berasal dari dua sumber, yaitu tanaman tomat yang positif terserang CMV (sap tanaman) dan kontrol positif CMV produsen AGDIA yang biasa digunakan sebagai kontrol positif pengujian DAS-ELISA (Double Antibody Sandwich-Enzyme Linked Immunosorbent assay). Penelitian ini bertujuan untuk menguji ketahanan tiga varietas tomat terhadap serangan CMV. Penelitian dilaksanakan di screen house dan laboratorium virologi Balai Besar Uji Standar Karantina Pertanian pada bulan Januari sampai April 2008. Identifikasi hasil penularan CMV dilakukan dengan mengamati periode inkubasi, gejala yang muncul, dan dilanjutkan dengan pengujian DAS-ELISA. Perlakuan disusun dengan rancangan acak lengkap (RAL) dengan 6 ulangan. Data diolah dengan analisis sidik ragam dan dilanjutkan dengan uji berganda Duncan pada taraf uji 5%. Hasil penelitian menunjukkan gejala penyakit hanya muncul pada varietas San Marino yang ditulari CMV asal sap tanaman. Gejala yang ditimbulkan berupa daun menggulung dan reduksi lamina daun dengan masa inkubasi 8-10 hari, serta gejala batang kerdil dengan masa inkubasi 14-28 hari, CMV pada San Marino menyebabkan reduksi tinggi tanaman sebesar 33%. Kesensitifan tomat varietas San Marino terhadap CMV asal sap tanaman secara kuantitatif dibuktikan dengan hasil yang positif pada pengujian DAS-ELISA. Sedangkan, varietas Marta F1 dan Viccario tahan terhadap penularan CMV asal sap tanaman maupun kontrol positif CMV produsen AGDIA.Kata kunci : Tomat (Solanum lycopersicum L.), Cucumber Mosaic Virus, metode DAS-ELISA